Ecological risks of novel environmental crop technologies using phytoremediation as an example - Angle, J. Scott; Linacre, Nicholas A. (International Food Policy Research Institute, 2005)
Phytoremediation is the use of living plants, known as hyperaccumulators which absorb unusually large amounts of metals in comparison to other plants. The use of classical plant breeding and new molecular techniques offers great potential to develop crops with the ability to clean up polluted sites. While these technologies have gained widespread attention, prior to commercial development, there are risks that must be considered – only a few of which have received even modest examination. Therefore, the focus of this working paper is to explore specific risks associated with phytoremediation and suggest ways in which these risks can be managed so that new, novel, and innovative plant technologies may be applied to provide low cost and efficient environmental solutions.-- Authors' Abstract